Real‐life experience of a stent‐less revascularization strategy using a combination of excimer laser and drug‐coated balloon for patients with acute coronary syndrome. (20th February 2018) - Harima, Ayako; Sairaku, Akinori; Inoue, Ichiro; Nishioka, Kenji; Oka, Toshiharu; Nakama, Yasuharu; Dai, Kazuoki; Ohi, Kuniomi; Hashimoto, Haruki; Kihara, Yasuki
Abstract : Objectives: We aimed to test a novel stent‐less revascularization strategy using a combination of excimer laser coronary angioplasty (ELCA) and drug‐coated balloon (DCB) for patients with acute coronary syndrome (ACS). Background: Percutaneous coronary intervention with drug eluting stents is a standard invasive treatment for ACS. Some unsolved issues however remain, such as stent thrombosis and bleeding risks associated with dual antiplatelet therapy. Methods: Consecutive ACS patients were planned to receive either a DCB application following ELCA without a stent implantation or conventional revascularization with a coronary stent. The endpoints were (i) major cardiac adverse events (MACEs), defined as the composite of cardiac death, myocardial infarctions, and target lesion revascularization; (ii) target vessel revascularization (TVR); and (iii) angiographic outcome. Results: Since a greater than expected number of patients allocated to the stent‐less treatment arm eventually received a bailout stenting, the following 3 as‐treated groups were compared; DCB with ELCA group ( N = 60), Stent with ELCA group ( N = 23), and Stent without ELCA group ( N = 85). During a mean follow‐up period of 420 ± 137 days, and with angiographic 6‐ and 12‐month‐follow‐up rates of 96.7%, 87%, and 81.2%, and 50%, 65.2%, and 45.9%, respectively, the MACE rate did not differ across the groups (10%, 4.3%, and 3.5%; P = 0.22) while an incidence of TVR was more common (15%, 0, and 4.7%; P = 0.02) and the diameter stenosis at 6‐months of follow‐up was greater (25.7 ± 18.2, 14.9 ± 13.1 and 16.2 ± 15.4%; P = 0.002) in the DCB with ELCA group. Conclusions: The stent‐less revascularization strategy with DCB and ELCA was associated with a higher occurrence of restenosis in ACS patients.